Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
Home  >>  CBSE XII  >>  Math  >>  Differential Equations
0 votes

The solution of the differential equation $y dx + (x + xy) dy = 0$ is

$\begin{array}{1 1} (A)\;ce^{y}=xy \\ (B)\;ce^{-y}=xy \\ (C)\;ce^{-y}=x+y \\ (D)\;ce^{-y}=x-y\end{array}$

Can you answer this question?

1 Answer

0 votes
  • A linear differential equation of the form $\large\frac{dy}{dx}$$=f(x),$ can be solved by seperating the variables and then integrating it
  • $\int \large\frac{1}{x}$$=\log |x|+c$
$ydx+(x+xy)dy=0$ is
This can be written as
(ie) $x(1+y)dy=-ydx$
Seperating the variables we get,
$\large\frac{(1+y)dy}{y}=- \frac{dx}{x}$
Now seperating the terms and integrating,
$\int \large\frac{1}{y} $$dy+\int dy=-\int \large\frac{dx}{x}$
$=>\log y+y=-\log x+c$
(ie) $\log y+y=-\log x+c$
$=>\log x+\log y=-y+c$
(or) $\log xy=-y+c$
$ce^{-y}=xy$ is the required solution .
Hence the solution of the differential equation
$ydx+(x+xy)dy=0$ is $ce^{-y}=xy$
answered May 22, 2013 by meena.p
Ask Question
student study plans
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App